The Influence of Service Quality, Patient Trust on Patient Loyalty by Mediating Patient Satisfaction at Aesthetic Clinics in the Bandung Area, West Java - Rosali, Alexandrina Everdine; Margaretha, Yolla (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
With more cosmetic clinics opening, competition is high, making patient loyalty important for long-term success. This study will examine service quality, trust, and loyalty through patient pleasure. This quantitative study using Structural Equation Modelling (SEM-PLS) on 189 patients found that trust and service quality increased patient loyalty. Patient satisfaction mediates well. Patients are happier and more loyal when they trust the service. This study supports prior findings that patient happiness is a vital component of the trust-loyalty-service-quality triangle. Staff training, queue management, and personalised care can help clinics gain patients’ trust and satisfaction. Data subjectivity and regional bias weaken the study. These findings suggest combining service quality, patient confidence, and patient satisfaction to retain patients in a competitive business. Future research should examine cultural and psychological factors to explain these findings